CTS-D certified technology specialist-design exam guide - Ciddor, Andy (ITpro collection, 2023)
The most up to date CTS-D exam study system--available exclusively from McGraw Hill and AVIXA Press Published with AVIXA®, CTS-D® Certified Technology Specialist-Design Exam Guide, Second Edition provides comprehensive coverage of all exam objectives on the leading internationally recognized certification for audiovisual design professionals. Each chapter features learning objectives, best practices, diagrams, photos, and chapter review questions with in-depth explanations. Designed to help you prepare for the CTS-D exam, this authoritative resource also serves as an essential on-the-job reference. Online content includes: New CTS-D sample questions from AVIXA Link to a library of design, installation, and AV math videos Link to AVIXA standards Link to AVIXA's AV standards Clearing House Covers all CTS-D exam objectives, including: Communicating design intent Ergonomics in AV design Audio and visual principles of design Communicating with allied trades Lighting specifications Structural and mechanical considerations Specifying electrical infrastructure Elements of acoustics Digital signals Audio and digital video design Control requirements Networking for AV Streaming design Security for networked AV applications Project implementation activities.